An Investigation of Chinese Audiences’ Attitude and Purchase Intention towards Product Placement in Reality Television Shows - Chen, Shanwen (2020)
As a popular alternative advertising format to reach customers, product placement has been increasingly important in marketing practices, such as product promotion, and many studies have investigated consumers’ attitude towards product placement in American movies. However, few researches have used theoretical frameworks to investigate the consumers’ attitude and purchase intention towards product placement in other countries and media contents. Therefore, mainly based on the consumer socialization theory and the balance model of product placement effects, this research aims to investigate the influences of peer communication, television watching time and audiences’ favourable attitude towards characters on Chinese audiences’ attitude and purchase intention towards product placements in the reality television show. Using the online questionnaire, the research has collected data from 199 Chinese reality television audiences, and findings show that peer communication and audiences’ favourable attitude towards characters can positively influence both consumers’ product placement attitude and their purchase intention to the placed products in Chinese reality television. However, there is no significant relationships between television watching time and consumers’ product placement attitude and purchase intention in the context of Chinese reality television. Besides, analyses from respondents’ comments about the use of product placement can help marketers or media producers to deeper understand the Chinese consumers product placement attitude and purchase intention and have better product placement practices in the reality television.